Great radiologic imitators: Arteriovenous malformation of mandible - A case series - A K Nabeel; Jesmith Elsa Jacob; Tinky Bose; K P Sangeetha; K N Sandhya; Anita Balan (Wolters Kluwer Medknow Publications, 2018)
An arteriovenous malformation (AVM) is a vascular malformation characterized by anomalous communications between arteries and veins without the normal intervening capillary bed. AVMs of jaw are extremely rare conditions that can give rise to dreadful complications if handled carelessly. Fifty percent of all intraosseous AVMs occur in the maxillofacial region and are extremely infrequent in the mandible. Only six cases of extraosseous submandibular AVMs have been mentioned in the literature. Three cases of AVMs involving the mandible, with a massive case involving both the mandible and submandibular region is reported. To the best of our knowledge, only one case is documented as a combined AVM involving both the mandible and submandibular region in literature.